Zenobia: CODIS 13 STR Loci Allele Detection Tool - Alrouwab, Osamah; Algblawi, Esraa; Kareem, Moudah; Aboujildah, Sabreen; Ayad , Saifedden; Gargotti , Mahmoud (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Short tandem repeats (STRs) are one of the most mutable regions in the human genome. They comprise tandem repeating DNA sequences ranging in length from two to six base pairs. Owing to their significant mutation rate, they exhibit considerable variation in pattern among populations and the capacity to be passed on from generation to generation. These loci are broadly employed in medicine, biology, and criminal investigation. They are pivotal in the genesis of a variety of genetic illnesses and have been intensively investigated in forensics, population genetics, and genetic genealogy. Although many implementations that manage STR loci are offered, most of them rely primarily on the command-line interface (CLI) inputs, which frequently necessitate the implementation of tools carried out in various scripting languages. Installing and launching programs through the command line (CL) is time-consuming and/or unprofitable for many students and scholars. The fundamental intention of this project is to develop a cross-platform graphical user interface (GUI) package directed at the Combined DNA Index System (CODIS) STR analysis. Zenobia is a Java-based application considered a step in consistently making CL-only programs available to more apprentices and researchers. Methods. Zenobia core dataset imported from STRBase, a public dataset provided by the National Institute of Standards and Technology. Only CODIS 13 STR markers data were elected. Zenobia uses the brute force approach to match recorded allele patterns in order to discover locus names and allele counts. Results. A set of 78 alleles took part in the trial, with 61.5% representing a simple STR subcategory. Additionally, 30.1% and 7.7% of nominees, respectively, were associated with the compound and complex STR subcategories. Conclusion. In general, Zenobia’s application outcomes satisfy the evaluation metrics for efficiency and time consumption. However, more genetic markers should be introduced to increase the productivity of the application.